Presentation: Investigating and Reviving the Early Nineteenth-Century Practice of Piano Arrangement: The Case of Haydn’s “Die Vorstellung des Chaos” and Beethoven’s Eroica Symphony - Montebugnoli, Luca (Ghent Orpheus Instituut, 2024)
This presentation examined the wave of piano reductions of Haydn’s Die Schöpfung published between 1800 and 1801, emphasizing the diversity among seven versions issued by musicians such as Müller, Neukomm, Clementi, and Steibelt. Focusing on the opening movement, “Die Vorstellung des Chaos,” the analysis compared the arrangers’ differing strategies and considered how their choices were shaped by the piano technologies of the time. The study highlighted how each version reinterprets the oratorio’s narrative and reflects the broader pianistic and cultural contexts of the early nineteenth century. The presentation concluded with a discussion of my arrangement of the fourth movement of Beethoven’s Eroica Symphony, conceived for a replica of the 1803 Erard piano owned by the composer.
FRIS
0
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850